Contact Allergens in Top-Selling Textile-care Products. Issue 1 (January 2020) - Bai, Heidi; Tam, Idy; Yu, JiaDe
Abstract : Background: Chemicals in textile manufacturing and laundering products are important sources of allergens triggering allergic contact dermatitis. Allergens corresponding to the textile production process have been well recognized. However, there is limited information regarding potential allergens in laundering products. Objective: The aim is to investigate the presence and prevalence of potential allergens in commonly used laundering products. Methods: An Internet-based search was performed to identify the current best-selling laundering products in the United States. Subsequent inquiry of common allergens for each product was collected through a review of ingredients listed by manufacturers. Results: Sixty-five laundering products were examined: 30 laundry detergents, 10 fabric softeners, 8 dryer sheets, and 17 stain removers. Ten common allergens were identified: benzisothiazolinone, benzyl benzoate, cocamidopropyl betaine, decyl glucoside, "fragrances, " lauryl glucoside, methylisothiazolinone, methylchloroisothiazolinone, phenoxyethanol, and propylene glycol. Fragrances and essential oils are the top allergens in laundry detergents (66.7%), fabric softeners (90%), dryer sheets (75%), and stain removers (58.8%). Laundry detergents labeled as "baby safe" and "free and gentle" contained common allergens, with methylisothiazolinone being the most prevalent, in 80% and 57.1%, respectively. Conclusions: Textile dermatitis can negatively impact quality of life and function. Aside from textile dyes and finishing resins, laundering products should also be considered.